POTENTIAL UTILITY OF FOVEAL MORPHOLOGY IN PRETERM INFANTS MEASURED USING HAND-HELD OPTICAL COHERENCE TOMOGRAPHY IN RETINOPATHY OF PREMATURITY SCREENING. Issue 8 (August 2020) - Anwar, Samira; Nath, Mintu; Patel, Aarti; Lee, Helena; Brown, Samantha; Gottlob, Irene; Proudlock, Frank A.
Abstract : Purpose: To investigate dynamic foveal morphology with postmenstrual age, in preterm infants with and without retinopathy of prematurity using hand-held optical coherence tomography, adjusting for gestational age (GA) and birthweight (BW). Methods: Prospective mixed cross-sectional/longitudinal observational study of 87 participants (23–36 weeks GA; n = 30 with, n = 57 without retinopathy of prematurity) using hand-held optical coherence tomography images (n = 278) acquired between 31 weeks and 44 weeks postmenstrual age excluding treated retinopathy of prematurity. Measurements included foveal width, area, depth, central foveal thickness, maximum slope, and parafoveal retinal thickness at 1, 000 µ m nasal and temporal to the central fovea. Results: Retinopathy of prematurity was significantly correlated with only foveal width in either GA or BW adjusted statistical models. In contrast, severity of prematurity (GA, BW) correlated with foveal area ( P < 0.005), depth ( P ⩽ 0.001), and slope ( P < 0.01), although central foveal thickness ( P = 0.007) and parafoveal retinal thickness ( P < 0.001) correlated with GA, but not with BW. Conclusion: Foveal width is independent of GA and BW with potential in retinopathy of prematurity screening assessment using hand-held optical coherence tomography. Foveal morphology could be graded in prematurity during development, with possible implications for future management of preterm infants. Abstract : Supplemental Digital Content is Available in the Text.Hand-held optical coherence tomography in prematurity shows foveal depth, thickness and area correlate with severity of gestational age or birthweight rather than presence of retinopathy of prematurity. In contrast, foveal width is independent of gestational age and birthweight but not retinopathy of prematurity, and has potential in retinopathy of prematurity screening.